Mitogen-Activated Protein Kinase Phosphatase 2 Regulates the Inflammatory Response in Sepsis - Cornell, Timothy T. (American Society for Microbiology (ASM), 2010)
Sepsis results from a dysregulation of the regulatory mechanisms of the pro- and anti-inflammatory response to invading pathogens. The mitogen-activated protein (MAP) kinase cascades are key signal transduction pathways involved in the cellular production of cytokines. The dual-specific phosphatase 1 (DUSP 1), mitogen-activated protein kinase phosphatase-1 (MKP-1), has been shown to be an important negative regulator of the inflammatory response by regulating the p38 and Jun N-terminal protein kinase (JNK) MAP kinase pathways to influence pro- and anti-inflammatory cytokine production. MKP-2, also a dual-specific phosphatase (DUSP 4), is a phosphatase highly homologous with MKP-1 and is known to regulate MAP kinase signaling; however, its role in regulating the inflammatory response is not known. We hypothesized a regulatory role for MKP-2 in the setting of sepsis. Mice lacking the MKP-2 gene had a survival advantage over wild-type mice when challenged with intraperitoneal lipopolysaccharide (LPS) or a polymicrobial infection via cecal ligation and puncture. The MKP-2(−/−) mice also exhibited decreased serum levels of both pro-inflammatory cytokines (tumor necrosis factor alpha [TNF-α], interleukin-1β [IL-1β], IL-6) and anti-inflammatory cytokines (IL-10) following endotoxin challenge. Isolated bone marrow-derived macrophages (BMDMs) from MKP-2(−/−) mice showed increased phosphorylation of the extracellular signal-regulated kinase (ERK), decreased phosphorylation of JNK and p38, and increased induction of MKP-1 following LPS stimulation. The capacity for cytokine production increased in MKP-2(−/−) BMDMs following MKP-1 knockdown. These data support a mechanism by which MKP-2 targets ERK deactivation, thereby decreasing MKP-1 and thus removing the negative inhibition of MKP-1 on cytokine production.